Reducing The Incidence Of Postoperative Cognitive Dysfunction In Women Undergoing Cesarean Section During Spinal Anesthesia And Drug Sedation With Desmedetomidine - Khudoiberdieva Gulrukh Sobirovna (Academia One, 2024)
Postoperative cognitive dysfunction syndrome (POCD) refers to disorders of higher mental functions that can develop in the postoperative period and are caused by surgery and anesthesia, as defined by L.S. Rasmussen is a cognitive disorder that develops in the early and persists in the late postoperative periods, clinically manifested by memory impairment, difficulty concentrating (concentrating) attention and disturbances of other higher cortical functions (thinking, speech, etc.), confirmed by neuropsychological testing
Keywords: confirmed; dysfunction; disorders; higher